TEKNOLOGI AUGMENTED REALITY UNTUK ALAT PERAGA PEMBELAJARAN ANAK - Adrian Tri Pambudi; A. Akhmad Qashlim; UL Khairat (Journal Peqguruang: Conference Series, 2022)
Augmented technology is generally only used for games and here I am trying to research an application to recognize letters and numbers based on augmented reality. Where children can learn to recognize letters and numbers with 3D screen animations. This technology combines the real world and the virtual world. To overcome this problem, the author makes an application of augmented reality technology for android-based teaching aids for children. This study aims to make it easier for children to recognize letters and numbers with an attractive and easy-to-use animated display. The data collection process in designing this system uses a marker-based tracking method. The result of this research is an application that implements augmented reality technology using a marker-based tracking method which is designed to help students get information and education about the introduction of flat shapes in elementary schools.